Introduction to business - Madura, Jeff (South-Western College Publishing, 1998)
This innovative text emphasizes business concepts and strategy while still providing the plethora of definitions the course requires. Practical focus addresses how and why businesses operate the way they do, covering topics such as adding value and creating profits through a variety of skill-building projects. The Coca-Cola annual report is available with each copy of the text; exercises and discussion following each chapter reference the annual report and show practical applications of chapter topics. Small Business Survey provides a reality-based picture of how small business managers conduct day-to-day business. CHC: Small Business Dilemma tracks a College Health Club business from start-up through topics tied to each chapter in the text. Spotlight on Technology features show the integration of technology and business. The Surfing the Net feature provides a foundation for student comprehension of the Internet without requiring computer access; featured Internet URL addresses are listed at the end of each chapter. Unique software available with the text helps students learn to run their own business and invest in the stock of a business.